IMPROVING STUDENT SPEAKING SKILL THROUGH COMMUNICATIVEAPPROACH: (An Action Research of the Fifth Grade Students ofMI Islamiyah Gumukrejo Teras IN 2010/ 2011 Academic Year) - EKAWATI, FIKHI (2011)
This research is aimed at knowing whether or not teaching speaking skill through communicative approach is able to improve ability and achievement of Elementary School students'. The result of this study hopefully will give contribution in learning English. In this research, teaching speaking skill through communicative approach is used to increase students' motivation and their achievement in learning English. This research was carried out at MI Islamiyah Gumukrejo Teras Boyolali, especially in class fifth that consists of 12 students. In collecting the required data, the writer did observation, gave test, and analyze document. There were two cycle in this action research in which pre-test in the early meeting and post-test in the last meeting. She analyzed the data by comparing the result pre-test and post-test. The result pre-test and post-test is used to know the students' achievement. The mean of the students' achievement after the teacher gave the action 74,5% that belongs to good category and the students' mean score before the teacher did the action was 51, 15%. Based on the research finding, it can be concluded that teaching speaking skill through in teaching English could increase the students' motivation and achievement. Therefore, it is better for the students to study English carefully through practice and experience, and to be active and creative in learning English. While the teacher should teach the students through communicative approach, process considerable knowledge to manage an interesting classroom, and prepare the lesson they are going to teach as well as possible.